2003
DOI: 10.1542/peds.112.4.787
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Training and Job Market Trends: Results From the American Academy of Pediatrics Third-Year Resident Survey, 1997–2002

Abstract: Experiences of graduating residents over the past 6 years provide insights into changes in pediatric residency education and the pediatric workforce. Efforts by pediatric educators and academic leaders to increase community experiences and child advocacy and to encourage greater interest in pediatric subspecialty careers seem to be succeeding. Unfortunately, demand for general pediatricians is weakening, and residents are experiencing increasing debt burdens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 33 publications
1
36
1
Order By: Relevance
“…PIs chose this setting for several reasons: (1) pediatric resident practice sites provide care for more than one-fifth of the socioeconomically disadvantaged families in the United States, 44 who are at highest risk for childhood obesity; (2) resident physicians have been shown to be more sensitive to clinical behavior change than community-based physicians 45,46 ; (3) a majority of pediatric residents become practicing community-based physicians 47,48 ; and (4) academic practicebased research networks, particularly the Continuity Clinic Research Network, provide the potential for rapid dissemination and quality improvement. 49 Although we considered alternative intervention settings (eg, primary-care private practices, community health centers; familymedicine practices), none offered more optimal combinations of these attributes.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…PIs chose this setting for several reasons: (1) pediatric resident practice sites provide care for more than one-fifth of the socioeconomically disadvantaged families in the United States, 44 who are at highest risk for childhood obesity; (2) resident physicians have been shown to be more sensitive to clinical behavior change than community-based physicians 45,46 ; (3) a majority of pediatric residents become practicing community-based physicians 47,48 ; and (4) academic practicebased research networks, particularly the Continuity Clinic Research Network, provide the potential for rapid dissemination and quality improvement. 49 Although we considered alternative intervention settings (eg, primary-care private practices, community health centers; familymedicine practices), none offered more optimal combinations of these attributes.…”
Section: Settingmentioning
confidence: 99%
“…Intention-to-treat analyses of betweengroup differences will be performed by using generalized estimating equations, with adjustment for double clustering both at the level of the physician (pediatric resident) and at the level of the clinic, using a robust sandwich estimator to compute right variance-covariance matrix. Secondary analyses will examine betweengroup differences in the change of BMI z score at 24 months 47 Caregiver health literacy will be examined as a primary predictor in most generalized estimating equation analyses. Interaction between health literacy (low versus adequate) and study status (intervention versus control) will be examined to determine if literacy level is a significant effect modifier.…”
Section: Analytic Planmentioning
confidence: 99%
“…47 Practical aspects of ambulatory care including patient scheduling, telephone management, and cost-effectiveness are areas of relative weakness. 30,41 Changes in residency training over the last decade seem to have improved residents' self-reported preparation for assessing community needs, 48,49 participating in child advocacy efforts, 49,50 and pursuing subspecialty training. 49 The articles by Freed and colleagues in this supplement add to this nascent literature.…”
mentioning
confidence: 99%
“…30,41 Changes in residency training over the last decade seem to have improved residents' self-reported preparation for assessing community needs, 48,49 participating in child advocacy efforts, 49,50 and pursuing subspecialty training. 49 The articles by Freed and colleagues in this supplement add to this nascent literature. The Freed et al survey of 7882 pediatrics residents as part of the 2007 American Board of Pediatrics in-training examination 51 sheds light on the pediatrics residency experience.…”
mentioning
confidence: 99%
“…In an article by Shope et al, the authors list multiple citations in which residency graduates in pediatrics "consistently identified the need to have more education in school health, child advocacy, behavioral pediatrics, and accessing community resources." 1 Moreover, Cull et al 4 showed that despite the 1996 recommendations from the Residency Review Committee to increase training in child advocacy, only half of graduating residents in 2002 rated their educational experiences in this area as "very good" or better. It is for these reasons that the domains established in these articles come at such an opportune time.…”
mentioning
confidence: 99%